EFFICACY OF SEMONT MANOEUVRE VERSUS EPLEY MANOEUVRE IN BENIGN PAROXYSMAL POSITIONAL VERTIGO - ., Sohail Babar; Niazi, Sohail Babar (Pakistan Armed Forces Medical Journal, 2011)
Objective: To compare the efficacy of Semont manoeuvre versus Epley manoeuvre in the management of benign paroxysmal positional vertigo. Study design: Interventional Quasi experimental study Place and duration of study: ENT OPD Combined Military Hospital Rawalpindi from 1st January2007 till 30th June 2007. Results: Of the 30 cases managed by Semont manoeuvre, 25 showed complete relief of symptomsafter 01 month. Out of 30 cases managed by Epley manoeuvre, 28 cases showed complete recoveryafter 01 month. The results were compared by Chi square test, as the data was mainly qualitative innature. The results of both the groups were compared on day 3, day 7 and day 30, which revealedthat both the Semont and Epley manoeuvre are equally effective in treatment of BPPV. Conclusion: Both Epley and Semont manoeuvre are equally effective for treating the patients of benign paroxysmal positional vertigo.